2016
DOI: 10.3390/en10010019
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for the Detection of Long-Chain Fatty Acids in an Anaerobic Digestate Using a Quartz Crystal Sensor

Abstract: Abstract:In anaerobic digestion (AD), long-chain fatty acids (LCFAs) produced by hydrolysis of lipids, exhibit toxicity against microorganisms when their concentration exceeds several millimolar. An absorption detection system using a quartz crystal microbalance (QCM) was developed to monitor the LCFA concentration during an anaerobic digester's operation treating oily organic waste. The dissociation of the LCFAs considerably improved the sensor response and, moreover, enabled it to specifically detect LCFA fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Analytical techniques for LCFA detection involve complex sample processing followed by gas chromatography, which requires expensive instrumentation, time, and additional personnel training. Kobayashi et al 51 demonstrated the use of a quartz crystal sensor to monitor LCFA concentrations in AD processes. Further development of more easily employed methods of LCFA detection, such as a quartz crystal sensor, would likely be needed for feasible and widely recommended monitoring of palmitic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Analytical techniques for LCFA detection involve complex sample processing followed by gas chromatography, which requires expensive instrumentation, time, and additional personnel training. Kobayashi et al 51 demonstrated the use of a quartz crystal sensor to monitor LCFA concentrations in AD processes. Further development of more easily employed methods of LCFA detection, such as a quartz crystal sensor, would likely be needed for feasible and widely recommended monitoring of palmitic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the sugar analysis for the AH hydrolysate with heptane pretreatment did not identify the presence of rhamnose or galacturonic acid at a temperature of 120°C. The extracted compounds from the lipids present in the biomass may be capable of altering the pKa of the reaction medium (e.g., from short/long fatty acid and rhamnolipids) and then, possibly the water contained in the medium may affect the polymerization of the sugar acids and rhamnose during Soxhlet extraction (Kobayashi et al 2017;Soltani Dashtbozorg et al 2019). Scissoring of amorphous cellulose and hemicellulose compounds depends on the operating microwave temperature (Xia et al 2016;De Melo et al 2017).…”
Section: Tem Analysismentioning
confidence: 99%
“…The pKa of LCFA in water is estimated to be around 4.8 [37], but in 50% (v/v) ethanol-water mixtures (equivalent to a 0.24 mol fraction) the pKa rises to 7.0 [38]. Other authors state that pKa of C14, C16, and C18 fatty acids in water are in the range of 8.1-10.5 [9,39]. As the dissociation can occur at pH > pKa (allowing LCFA to dissolve easily in water) and the usual pH of wastewater is close to neutral, LCFA are insoluble in this medium and float on the surface.…”
Section: Effect Of Phmentioning
confidence: 99%
“…In the anaerobic digestion process, long-chain fatty acids (LCFA) such as myristic, palmitic, stearic, oleic, and linoleic acids are produced by lipid hydrolysis from the FOG found in wastewater [4]. LCFA can be present or anaerobically produced from dairy wastewater [5], oil wastewater [6], fish waste [7], slaughterhouse wastewater [8], and vegetable waste from restaurants [9] or food processing industries such as olive mill wastewater (OMW), the liquid by-product obtained from olive oil production [10].…”
Section: Introductionmentioning
confidence: 99%